A novel mathematical model of true ovarian reserve assessment based on predicted probability of poor ovarian response: a retrospective cohort study - Xu, Huiyu (J Assist Reprod Genet, 2020)
PURPOSE: To establish a mathematical model for assessing the true ovarian reserve based on the predicted probability of poor ovarian response (POR). METHODS: In this retrospective cohort study, a total of 1523 GnRH-antagonist cycles in 2017 were firstly analyzed. The ovarian responses were calculated based on the number of retrieved oocytes. The continuous variables were converted into categorical variables according to cutoff values generated by the decision tree method. The optimal model was identified using forward stepwise multiple logistic regression with 5-fold cross-validation and further verified its performances using outer validation data. RESULTS: The predictors in our model were anti-Müllerian hormone (AMH), antral follicle counts (AFC), basal follicle-stimulating hormone (FSH), and age, in order of their significance, named AAFA model. The AUC, sensitivity, specificity, positive predictive value, and negative predictive value of AAFA model in inner validation and outer validation data were 0.861 and 0.850, 0.603 and 0.519, 0.917 and 0.930, 0.655 and 0.570, and 0.899 and 0.915. Ovarian reserve of 16 subgroups was further ranked according to the predicted probability of POR and further divided into 4 groups of A–D using clustering analysis. The incidence of POR in the four groups was 0.038 (0.030–0.046), 0.139 (0.101–0.177), 0.362 (0.308–0.415), and 0.571 (0.525–0.616), respectively. The order of ovarian reserve from adequate to poor followed the order of A to D. CONCLUSION: We have established an easy applicable AAFA model for assessing true ovarian reserve and may have important implications in both infertile women and general reproductive women in Chinese or Asian population. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10815-020-01700-1) contains supplementary material, which is available to authorized users.